Spiroconjugated Tetraaminospirenes as Donors in Color‐Tunable Charge‐Transfer Emitters with Donor‐Acceptor Structure. Issue 6 (16th December 2021) - Grenz, David C.; Rose, Daniel; Wössner, Jan S.; Wilbuer, Jennifer; Adler, Florin; Hermann, Mathias; Chan, Chin‐Yiu; Adachi, Chihaya; Esser, Birgit
Abstract: Charge‐transfer emitters are attractive due to their color tunability and potentially high photoluminescence quantum yields (PLQYs). We herein present tetraaminospirenes as donor moieties, which, in combination with a variety of acceptors, furnished 12 charge‐transfer emitters with a range of emission colors and PLQYs of up to 99 %. The spatial separation of their frontier molecular orbitals was obtained through careful structural design, and two DA structures were confirmed by X‐ray crystallography. A range of photophysical measurements supported by DFT calculations shed light on the optoelectronic properties of this new family of spiro‐NN‐donor‐acceptor dyes. Abstract : Emitters go spiro : Using spiroconjugated tetraamines as a novel type of donor and a range of different acceptors in three different modes of connection, 12 donor‐acceptor compounds are synthesized. Their twisted structures lead to a spatial separation of the HOMOs and LUMOs. Photophysical measurements show tunable emission colors for these donor‐acceptor compounds, and photoluminescence quantum yields of up to 99 % in solution are obtained.